2014
DOI: 10.3389/fpsyg.2014.00904
|View full text |Cite
|
Sign up to set email alerts
|

Reflexive anaphor resolution in spoken language comprehension: structural constraints and beyond

Abstract: We report results from an eye-tracking during listening study examining English-speaking adults’ online processing of reflexive pronouns, and specifically whether the search for an antecedent is restricted to syntactically appropriate positions. Participants listened to a short story where the recipient of an object was introduced with a reflexive, and were asked to identify the object recipient as quickly as possible. This allowed for the recording of participants’ offline interpretation of the reflexive, respo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
20
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(21 citation statements)
references
References 29 publications
1
20
0
Order By: Relevance
“…The results of the above cited studies are mixed. In antecedent-match conditions, increased processing difficulty due to the presence of a cue-matching distractor has been reported by Badecker and Straub ( 2002 ), Experiments 3, 4, Chen et al ( 2012 ), Clackson and Heyer ( 2014 ), Jäger et al ( 2015 ), Experiment 2, and Patil et al (unpublished manuscript). By contrast, Sturt ( 2003 ), Experiment 1, and Cunnings and Felser ( 2013 ), Experiment 2 found a facilitation due to a cue-matching distractor.…”
Section: Introductionmentioning
confidence: 55%
See 2 more Smart Citations
“…The results of the above cited studies are mixed. In antecedent-match conditions, increased processing difficulty due to the presence of a cue-matching distractor has been reported by Badecker and Straub ( 2002 ), Experiments 3, 4, Chen et al ( 2012 ), Clackson and Heyer ( 2014 ), Jäger et al ( 2015 ), Experiment 2, and Patil et al (unpublished manuscript). By contrast, Sturt ( 2003 ), Experiment 1, and Cunnings and Felser ( 2013 ), Experiment 2 found a facilitation due to a cue-matching distractor.…”
Section: Introductionmentioning
confidence: 55%
“…To summarize, for materials as the ones presented in (3), both encoding interference and cue-based retrieval interference predict that a matching distractor leads to a processing slow-down in antecedent-match conditions and to a speed-up in antecedent-mismatch conditions. For online reading time measures, both accounts thus make precisely the same predictions and can account for the inhibitory effects in antecedent-match conditions reported by Badecker and Straub ( 2002 ), Chen et al ( 2012 ), Clackson and Heyer ( 2014 ), Jäger et al ( 2015 ) and Patil et al (unpublished manuscript) as well as for the facilitatory effects in antecedent-mismatch conditions reported by King et al ( 2012 ) and Parker and Phillips ( 2014 ). For retrieval probabilities (to be reflected in response accuracies of adequate comprehension questions), both accounts also make the same predictions for antecedent-match conditions but differ in their predictions for antecedent-mismatch conditions.…”
Section: Introductionmentioning
confidence: 64%
See 1 more Smart Citation
“…Some studies have found no evidence for the activation of syntactically incorrect potential antecedents in the case of reflexives (cross-modal priming: Nicol, 1988; Nicol & Swinney, 1989; eye tracking during listening: Clackson, Felser, & Clahsen, 2011; event-related potential: Xiang, Dillon, & Phillips, 2009), while other results support the activation of multiple potential antecedents for reflexives as well (self-paced reading: Badecker & Straub, 2002; eye-tracking during reading: Cunnings & Felser, 2013; eye-tracking during listening: Clackson & Heyer, 2014). Although Clackson and Heyer (2014) also emphasize that the effect is stronger in the case of pronouns, they argue that the lack of evidence for multiple potential antecedents during reflexive processing in other studies is due to a methodological flaw. Overall, online sentence comprehension studies suggest that when there is a prominent potential antecedent in the discourse context during the processing of reflexives and pronouns, the processing system does not rule it out immediately even if it is inappropriate based on binding principles.…”
Section: Processing Anaphors In Sentencesmentioning
confidence: 96%
“…However, this issue is currently impossible to RETRIEVAL INTERFERENCE: META-ANALYSIS 26 quantitatively address in the meta-analysis as not enough data are available.Reflexive-/reciprocal-antecedent dependenciesTarget-match configurations. Among the studies that did observe significant effects in target-match configurations, most found inhibitory interference(Jäger et al, 2015, Experiment 1; Felser et al, 2009, c-command cue; Badecker & Straub, 2002, Experiments 3, 4;Patil, Vasishth, & Lewis, 2016;Clackson & Heyer, 2014). By contrast, facilitatory interference was found inSturt (2003, Experiment 1), and inCunnings and Felser (2013, Experiment 2, participants with low working memory capacity).…”
mentioning
confidence: 98%